STUDENTS’ ACCEPTANCE TO USING GRAPHIC NOVELS IN LEARNING LITERATURE (L2): A MALAYSIAN CASE STUDY - Abu Yazid Abu Bakar; Dayang Nurfaezah Abang Ahmad; Melor Md Yunus (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
Research has shown that using graphic novels in the classroom is one of useful approaches to promote the understanding of learners especially for lengthy and difficult literature texts. This study reports the extent of graphic novel in facilitating students’ understanding of literature and the students’ perceptions towards using graphic novel in learning literature (L2) as compared to other genre of texts. This is a mixed method study which employs quantitative and qualitative methods to obtain data. The findings indicate that most students found that graphic novel helped them to enrich their vocabularies and understand the text better. The findings also reveal that students were attracted to the illustrations in the literature text in which this helps to boost their motivation to learn literature in the classroom. The findings provide useful insights for English as Second Language (ESL) teachers in incorporating and expanding the literature learning through graphic novels in the future. The findings also imply the need of ESL teachers to use graphic novels effectively in facilitating their teaching and learning of literature in L2 classrooms particularly to suit the 21st century teaching and learning.